Influência de macro-fatores na estruturação da comunidade zooplanctônica em riachos subtropicais. - Aggio, Carlos Eduardo Gonçalves (2015)
The comprehension of the ecological structure and the functioning of natural and/or impacted lotic ecosystems is the purpose of most studies concerning rivers and streams. This study aimed to investigate the main factors influencing the zooplankton community organization in nine impacted tropical streams of three different sub-basins of the Cinzas River basin, Paraná state, Brazil. In this context, we tested the hypothesis that macro-factors such as productivity, current velocity, habitat structure, the stream order and stretches (headwater, middle and mouth), are the main factors structuring the zooplankton community in tropical streams. Zooplankton was represented by 101 taxa, mainly testate amoebae, followed by rotifers, cladocerans and copepods. Results evidenced that, among the evaluated factors, the zooplankton community, specially the abundance of testate amoebae and also microcrustaceans, responded to some degree of variation to the stream order. However, RDA results suggests that the great differentiation in the physical and chemical characteristics of the water, as well as those found in the zooplankton community structure, are related to a broad regional scale such as the differences observed among the three sub-basins studied.